PENGARUH KONFLIK ARTEMARSIAL DALAM MEMBANGUN KARAKTER SERTA IMPLIKASI KEBIJAKAN PUBLIK UNTUK PEMBERDAYAAN PEMUDA DI TIMOR LESTE - Odete da Costa Peloy; Antonio Martins Soares; Hugo Lourenço da Costa; Matinho Mendez Pereira; Tomas Pereira; Jose A. da Costa Belo Pereira (Jurnal Komunikasi Hukum, 2025)
The problems faced by the Timorese nation in the era of globalization are very complex, this is evidenced by the various social problems that have hit the Timorese community so that there have been many shifts in values ​​that have grown in society. Based on this study using a qualitative approach with case studies in several communities in Timor Leste that have implemented the artemarsial program. The results of the data analysis show that of the 13 districts from which data was taken, the most significant increase in the graph in the Dili district had the highest number of conflicts with 987 cases, followed by Ainaro with 200 cases, and Viqueque with 155 cases. The results of the study showed that young people involved in artemarsial training showed a significant reduction in aggressive behavior and were better able to manage conflicts in a more peaceful manner.